Haunting and transitional justice: on lives, landscapes and unresolved pasts - Lawther, Cheryl (International review of victimology, 2021)
This article explores practices of haunting and ghosting after conflict-related loss. This is not to suggest a focus on the occult or the paranormal, but to use these phenomena as a prism through which to understand the intersection between unresolved pasts and the transmission of trauma post-conflict. As Michael Levan notes, trauma lingers ‘unexorcisably in the places of its perpetration, in the bodies of those affected, in the eyes of the witnesses, and in the politics of memory’. The ghost, according to Avery Gordon ‘is the principal form by which something lost or invisible or seemingly not there makes itself known or apparent to us’. In this article I argue for three conceptualisations of haunting when past traumas remain unaddressed: the haunting of lost lives, the haunting of landscape, and the haunting presence of the unresolved past. The article focuses on Northern Ireland, a post-conflict jurisdiction described as being haunted by a ‘conflict calendar in which every day is an anniversary’ and extensive fieldwork with victims and survivors of the conflict. The article concludes by arguing that the presence of ghosts and the experience of haunting represent a ‘call to action’ in the quest to deal with a legacy of violent conflict and human rights abuses.